Important Elements and Features of Neighborhood Landscape for Aging in Place: A Study in Hong Kong - Shi, Shu-Lin (Frontiers in Public Health, 2020)
With a rapid growth of the aging population in the world, promoting aging in place has become more significant in recent years. Many neighborhood landscape elements and features have been revealed as critical to aging in place by accumulating research findings. However, they were usually studied separately or in small groups. Little has been done to examine relative importance of these elements and features when put together, from the older adults’ point of view. In this context, the current study investigated older adults’ perceived importance of 22 selected neighborhood landscape elements and features. A questionnaire survey was conducted in 17 public rental housing estates with proportions of older residents (aged 65 or above) between 20-40% in Hong Kong. According to 426 collected samples, landscape elements and features that contribute to comfort and help avoid hazards are considered highly important by older adults, such as good ventilation, good ventilation, avoid severe sunshine/rain, body support and good hygiene. While those potentially bring hazards while not necessities to older adults’ outdoor experience are considered least important, including portable chairs, outdoor tables, plants allow touching, close to children’s playground, small space for stay alone, water features and fitness equipment. After interpreting findings of perceived importance with other collected data integrally, some landscape design suggestions are generated to supplement existing guidelines and recommendations that concerning older adults’ well-being and quality of life. These findings would inspire future research and landscape design that prioritize promoting aging in place.